High-power plasma dynamic systems of quasi-stationary type in IPP NSK KIPT: results and prospects - Solyakov, D.G. (Вопросы атомной науки и техники, 2015)
This paper is devoted to brief review of main experimental results of investigations of high-power quasi-stationary plasma dynamic systems in the IPP NSC KIPT. In experiments were shown that to received accelerated plasma streams with high value of energy in quasi-stationary modes all conditions on the accelerating channel boundary should be controlled independently. As a results of optimizations of the modes of operation all QSPA active elements quasi-stationary plasma flow in the channel during 480 μs at discharge durations 550μs was obtained. The plasma streams velocity was close to theoretical limit for present experimental conditions. Plasma streams with maximum velocity up to 4.2·10⁷ cm/s and total value of energy containment in the stream 0.4…0.6 MJ were received. The main properties of compression zone formation in the plasma streams generated by magneto-plasma compressor in quasi-stationary modes were investigated. In experiments were shown that initial conditions, namely residual pressure in the vacuum chamber made a big influence on the value of plasma density in compression zone. Compressive plasma streams with density (2…4)·10¹⁸ cm⁻³ during 20…25μs at discharge duration 10μs were obtained. This value of plasma density is close to theoretical limit for present experimental conditions.